2022
DOI: 10.3233/shti220969
|View full text |Cite
|
Sign up to set email alerts
|

Management of Cancer Patients in the COVID-19 Crisis Using Telemedicine: A Systematic Review

Abstract: Background: Telemedicine can provide a solution for disease management during the COVID-19 pandemic. This literature review aims to explore the role of telemedicine during the COVID-19 pandemic for management of cancer patients. Method: A comprehensive systematic search was conducted in PubMed, Science Direct, EMBASE, and Web of Science databases for the papers published until April 2021. Studies were included in case they had practically used telemedicine in the management of cancer patients during the COVID-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Of the 51 included systematic reviews, 14 articles also included a quantitative analysis/meta-analysis with one being individual participant meta-analysis ( Dhada et al, 2021 ; Teglia et al, 2022a ; Teglia et al, 2022b ; Nikolopoulos et al, 2022 ; Zhang et al, 2022 ; Kirby et al, 2022 ; Donkor et al, 2021 ; Gascon et al, 2022 ; Hojaij et al, 2020 ; Legge et al, 2022 ; Murphy et al, 2022 ; Gadsden et al, 2022 ; Majeed et al, 2022 ; Adham et al, 2022 ; Alom et al, 2021 ; Ayubi et al, 2021 ; Garg et al, 2020 ; Jammu et al, 2021 ; Lu et al, 2021 ; Momenimovahed et al, 2021 ; Mostafaei et al, 2022 ; Moujaess et al, 2020 ; Muls et al, 2022 ; Pacheco et al, 2021 ; Rohilla et al, 2021 ; Salehi et al, 2022 ; Sun et al, 2021 ; Zapała et al, 2022 ; Alkatout et al, 2021 ; Di Cosimo et al, 2022 ; Fancellu et al, 2022 ; Ferrara et al, 2022 ; Hesary and Salehiniya, 2022 ; Lignou et al, 2022 ; Mayo et al, 2021 ; Mazidimoradi et al, 2021 ; Mazidimoradi et al, 2022 ; Ng and Hamilton, 2022 ; Pararas et al, 2022 ; Riera et al, 2021 ; Sarich et al, 2022 ; Sasidharanpillai and Ravishankar, 2022 ; Tang et al, 2022 ; Thomson et al, 2020 ; Vigliar et al, 2020 ; de Bock et al, 2022 ). Other key characteristics of the 51 systematic reviews are shown in Table 1 (more extensive details appear in Supplementary file 1a and Supplementary file 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the 51 included systematic reviews, 14 articles also included a quantitative analysis/meta-analysis with one being individual participant meta-analysis ( Dhada et al, 2021 ; Teglia et al, 2022a ; Teglia et al, 2022b ; Nikolopoulos et al, 2022 ; Zhang et al, 2022 ; Kirby et al, 2022 ; Donkor et al, 2021 ; Gascon et al, 2022 ; Hojaij et al, 2020 ; Legge et al, 2022 ; Murphy et al, 2022 ; Gadsden et al, 2022 ; Majeed et al, 2022 ; Adham et al, 2022 ; Alom et al, 2021 ; Ayubi et al, 2021 ; Garg et al, 2020 ; Jammu et al, 2021 ; Lu et al, 2021 ; Momenimovahed et al, 2021 ; Mostafaei et al, 2022 ; Moujaess et al, 2020 ; Muls et al, 2022 ; Pacheco et al, 2021 ; Rohilla et al, 2021 ; Salehi et al, 2022 ; Sun et al, 2021 ; Zapała et al, 2022 ; Alkatout et al, 2021 ; Di Cosimo et al, 2022 ; Fancellu et al, 2022 ; Ferrara et al, 2022 ; Hesary and Salehiniya, 2022 ; Lignou et al, 2022 ; Mayo et al, 2021 ; Mazidimoradi et al, 2021 ; Mazidimoradi et al, 2022 ; Ng and Hamilton, 2022 ; Pararas et al, 2022 ; Riera et al, 2021 ; Sarich et al, 2022 ; Sasidharanpillai and Ravishankar, 2022 ; Tang et al, 2022 ; Thomson et al, 2020 ; Vigliar et al, 2020 ; de Bock et al, 2022 ). Other key characteristics of the 51 systematic reviews are shown in Table 1 (more extensive details appear in Supplementary file 1a and Supplementary file 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Telehealth was investigated and reported in 12 of the included reviews ( Dhada et al, 2021 ; Hojaij et al, 2020 ; Murphy et al, 2022 ; Alom et al, 2021 ; Lu et al, 2021 ; Mostafaei et al, 2022 ; Salehi et al, 2022 ; Zapała et al, 2022 ; Di Cosimo et al, 2022 ; Lignou et al, 2022 ; Pascual et al, 2022 ; Bezerra et al, 2022 ); a summary of main findings is provided in Supplementary file 1h . Salehi et al, 2022 reported that telemedicine use in breast cancer patients was the most common investigated in studies exploring cancer-specific use of telemedicine. Telemedicine was used for various reasons, with provision of virtual visit services and consultation being the most common ( Salehi et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Telehealth was investigated and reported in 10 of the included reviews 2 10 12 19 23 25 30 32 34 38 ; a summary of main findings is provided in Appendix 11. Salehi F et al 2022 30 reported that telemedicine use in breast cancer patients was the most common investigated in studies exploring cancer-specific use of telemedicine. Telemedicine was used for various reasons, with provision of virtual visit services and consultation being the most common 30 .…”
Section: Telemedicinementioning
confidence: 99%
“…Salehi F et al 2022 30 reported that telemedicine use in breast cancer patients was the most common investigated in studies exploring cancer-specific use of telemedicine. Telemedicine was used for various reasons, with provision of virtual visit services and consultation being the most common 30 . One study explored various symptom tracking apps for cancer patients, available in the mobile health market, and found that only a limited number of apps exist for cancer-specific symptom tracking (27%) 23 .…”
Section: Telemedicinementioning
confidence: 99%